Macular Structure and Microvasculature Changes in AIDS-Related Cytomegalovirus Retinitis Using Optical Coherence Tomography Angiography - Du, Kui-Fang; Huang, Xiao-Jie; Chen, Chao; Kong, Wen-Jun; Xie, Lian-Yong; Wei, Wen-Bin (Frontiers in Medicine, 2021)
Background: Cytomegalovirus retinitis (CMVR) is the most common manifestation of AIDS-related ocular opportunistic infection. The CMVR lesions produced retinal necrosis. It is not entirely clear whether the CMVR eyes without macular-involved necrotic lesions may have subtle macular damages. In this study, we conducted a cross-sectional study using optical coherence tomography angiography (OCTA), to evaluate macular microvasculature and structure in eyes with AIDS-related CMVR. Methods: AIDS-related CMVR patients ( active and inactive CMVR ) and healthy controls in the Department of Ophthalmology, Beijing Youan Hospital, Capital Medical University between August 25, 2019, and October 18, 2019, were recruited. The whole OCTA parameters, including foveal avascular zone (FAZ), retinal vessel density (VD), choroidal vascularity index (CVI), retinal thickness, and choroidal thickness were compared between groups after the signal strength was corrected. Results: Signal strength in 3×3 mm and 6×6 mm scan patterns were significantly weaker in the inactive CMVR than in the control group (both p < 0.001). After adjusting for signal strength, heterogeneity in the central fovea and parafoveal quadrants was present with a shift toward lower macular chorioretinal vasculature, decreased full choroidal thickness, and thicker retinal thickness in the active and inactive CMVR group. The thickness of the retinal nerve fiber layer (RNFL) and inner nuclear layer (INL) was significantly thicker in active and inactive CMVR when comparing with the control group (all p < 0.05). For PR-RPE thickness, no significant differences were found in all quadrants between groups. FAZ areas showed no difference between the three groups (p = 0.053). Conclusions: Subtle macular structure and microvasculature damages still exist in CMVR eyes without macular-involved necrotic lesions. The results of our study are helpful to a deep understanding of the damages of CMVR.